Regulation of virus-associated lymphoma growth and gene expression by bacterial quorum-sensing molecules - Qiao, Jing (2018)
Kaposi's sarcoma-associated herpesvirus (KSHV) can cause several human cancers, including primary effusion lymphoma (PEL), which frequently occur in immunocompromised patients. KSHV-infected patients often suffer from polymicrobial infections caused by opportunistic bacterial pathogens. Therefore, it is crucial to understand how these coinfecting microorganisms or their secreted metabolites may affect KSHV infection and the pathogenesis of virus-associated malignancies. Quorum sensing (QS), a cell density-based intercellular communication system, employs extracellular diffusible signaling molecules to regulate bacterial virulence mechanisms in a wide range of bacterial pathogens, such as Pseudomonas aeruginosa, which is one of the most common opportunistic microorganisms found in immunocompromised individuals. In this study, we evaluated and compared the influence on PEL growth and the host/viral interactome of the major QS signaling molecules [N-(3-oxododecanoyl)-L-homoserine lactone (OdDHL), N-butyrylhomoserine lactone (BHL), and 2-heptyl-3-hydroxy-4-quinolone (PQS)] in conditioned medium from wild-type (wt) and QS mutant laboratory strains as well as clinical isolates of P. aeruginosa. Our data indicate that P. aeruginosa coinfection may facilitate virus dissemination and establishment of new infection and further promote tumor development through effectively inducing viral lytic gene expression by its QS systems.